Implementasi Steganografi untuk Keamanan Jaringan Teknik Tersembunyi dalam Komunikasi Data - Muh Rizky Anggara Yunan Putra; Bintang Putra Aryatama; Nikodemus Christiano David; Gilang Pamungkas; Indrawan Ady Saputro (Jurnal Riset Multidisiplin Edukasi, 2025)
In the current digital era, where data threats are increasingly sophisticated and varied, network security measures such as steganography are essential. Steganography is a method used to conceal information within other media, such as images, audio, or video, so that the existence of the information is not detected by unauthorized parties. This method aims to maintain the confidentiality of the embedded message, ensuring that only the sender and the recipient are aware of its content. This research employs a literature study involving the collection of data from various sources, reading, noting, and processing the research materials. The results indicate that the implemented steganography method successfully embeds data with a low detection rate by third parties while maintaining good image quality. However, performance varies depending on the format and size of the digital media used. Overall, the implemented steganography method has proven effective in concealing sensitive data within digital media without compromising the quality of the media.